See me, Feel me, Touch me, Heal me: Wind turbines, culture, landscapes, and sound impressions. (July 2015) - Firestone, Jeremy; Bates, Alison; Knapp, Lauren A.
Highlights: We evaluate social, sound and visual impacts regarding a community wind project. The majority of residents hold positive attitudes for visual appeal and for the project overall. Positive opinion on the look of the wind turbine reflects a transformation to a clean energy future. Negative opinion of the look of the wind turbine reflects that the turbine does not fit the landscape. Public opinions reflect socially and culturally constructed aspects of the wind turbine. Abstract: Community-based wind energy projects, with their small-scale, yet sizeable presence, provide a valuable opportunity to understand how individuals make sense of changes to their communities and to the surrounding landscape. Here, we examine the results of a 2013 mail survey of individuals residing in the vicinity of a 2 MW wind turbine that is located on the edge of the historic coastal town of Lewes, Delaware in the United States, and adjacent to Delaware Bay and the Great Marsh Preserve. The wind turbine, which was constructed in 2010, primarily serves the University of Delaware's coastal campus, and to a lesser extent the town of Lewes. Seventy-eight percent hold positive or very positive attitudes toward the wind turbine, with only 10% having negative or very negative attitudes, and 82% like the look of the wind turbine. Socially constructed aspects find more resonance than physical ones (e.g., attractiveness) in explaining this latter finding, with the wind turbine being reflective of a transformation to a clean energy future for those residents who like the way the turbine looks. On the other hand, those objecting to its look, find the turbine does not fit the landscape. Policy implications of these findings and others related to wind turbine sound are considered, and recommendations for better understanding of proposed developments from the vantage point of the affected communities, including how a community views itself and its surrounding landscape, are made.